Activation of SO2 and CO2 by trivalent uranium leading to sulfite/dithionite and carbonate/oxalate complexes. - Schmidt, Anna-Corina; Heinemann, Frank Wilhelm; Kefalidis, Christos E.; Maron, Laurent; Roesky, Peter W.; Meyer, Karsten (Chemistry - A European Journal, 2014)
The first sulfite [(((nP,Me) ArO)3 tacn)U(IV) 2 (μ-κ(1) :κ(2) -SO3 )] (tacn=triazacyclononane) and dithionite [(((nP,Me) ArO)3 tacn)U(IV) 2 (μ-κ(2) :κ(2) -S2 O4 )] complexes of uranium from reaction with gaseous SO2 have been prepared. Additionally, the reductive activation of CO2 was investigated with respect to the rare oxalate [(((nP,Me) ArO)3 tacn)U(IV) 2 (μ-κ(2) :κ(2) -C2 O4 )] formation. This ultimately provides the unique S2 O4 (2-) /C2 O4 (2-) and SO3 (2-) /CO3 (2-) complex pairs. All new complexes were characterized by a combination of single-crystal X-ray diffraction, elemental analysis, UV/Vis/NIR electronic absorption, IR vibrational, and (1) H NMR spectroscopy, as well as magnetization (VT SQUID) studies. Moreover, density functional theory (DFT) calculations were carried out to gain further insight into the reaction mechanisms. All observations, together with DFT, support the assumption that SO2 and CO2 show similar (dithionite/oxalate) to analogous (sulfite/carbonate) activation behavior with uranium complexes.

Activation of SO2 with [(η5-C5Me5)2Ln(THF)2] (Ln=Eu, Yb) leading to dithionite and sulfinate complexes - Klementyeva, Svetlana V.; Gamer, Michael T.; Schmidt, Anna-Corina; Meyer, Karsten; Konchenko, Sergey N.; Roesky, Peter W. (Chemistry - A European Journal, 2014)
The reaction of decamethylytterbocene [(η5-C5Me5)2Yb(THF)2] with SO2 at low temperature gave two new compounds, namely, the YbIII dithionite/sulfinate complex [(η5-C5Me5)2Yb(μ3,1κ2O1,3,2κ3O2,2′,4-S2O4)2(η5-C5Me5)Yb(μ,1κO,2κO′-C5Me5SO2)2] (1) and the YbIII dithionite complex [(η5-C5Me5)2Yb2(μ,1κ2O1,3,2κ2O2,4-S2O4)] (2). After extraction of 1, the mixture was heated to give the dinuclear tetrasulfinate complex [(η5-C5Me5)Yb2(μ,κO,κO'-C5Me5SO2)4] (3 a). In contrast, from the reaction of [(η5-C5Me5)2Eu(THF)2] with SO2 only the tetrasulfinate complex [(η5-C5Me5)Eu2(μ,κO,κO'-C5Me5SO2)4] (3 b) was isolated. Two major reaction pathways were observed: 1) reductive coupling of two SO2 molecules to form the dithionite anion S2O42-; and 2) nucleophilic attack of one metallocene C5Me5 ligand on the sulfur atom of SO2. The compounds presented are the first dithionite and sulfinate complexes of the f-elements.
CRIS-Team Scopus Importer:2020-09-14
Keywords: dithionite complexes; lanthanides; rare earths; reduction; SO

A series of uranium (IV, V, VI) tritylimido complexes, their molecular and electronic structures and reactivity with CO2. - Schmidt, Anna-Corina; Heinemann, Frank Wilhelm; Maron, Laurent; Meyer, Karsten (Inorganic Chemistry, 2014)
A series of uranium tritylimido complexes with structural continuity across complexes in different oxidation states, namely U(IV), U(V), and U(VI), is reported. This series was successfully synthesized by employing the trivalent uranium precursor, [(((nP,Me)ArO)3tacn)U(III)] (1) (where ((nP,Me)ArO)3tacn(3-) = trianion of 1,4,7-tris(2-hydroxy-5-methyl-3-neopentylbenzyl)-1,4,7-triazacyclononane), with the organic azides Me3SiN3, Me3SnN3, and Ph3CN3 (tritylazide). While the reaction with Me3SiN3 yields an inseparable mixture of both the azido and imido uranium complexes, applying the heavier Sn homologue yields the bis-μ-azido complex [(((nP,Me)ArO)3tacn)U(IV)2(μ-N3)2] (2) exclusively. In contrast to this one-electron redox chemistry, the reaction of precursor 1 with tritylazide solely leads to the two-electron oxidized U(V) imido [(((nP,Me)ArO)3tacn)U(V)(N-CPh3)] (3). Oxidation and reduction of 3 yield the corresponding U(VI) and U(IV) complexes [(((nP,Me)ArO)3tacn)U(VI)(N-CPh3)][B(C6F5)4] (4) and K[(((nP,Me)ArO)3tacn)U(IV)(N-CPh3)] (5), respectively. In addition, the U(V) imido 3 engages in a H atom abstraction reaction with toluene to yield the closely related amido complex [(((nP,Me)ArO)3tacn)U(IV)(N(H)-CPh3)] (6). Complex 6 and the three tritylimido complexes 3, 4, and 5, with oxidation states ranging from +IV to +VI and homologous core structures, were investigated by X-ray diffraction analyses and magnetochemical and spectroscopic studies as well as density functional theory (DFT) computational analysis. The series of structurally very similar imido complexes provides a unique opportunity to study electronic properties and to probe the uranium imido reactivity solely as a function of electron count of the metal-imido entity. Evidence for the U-N bond covalency and f-orbital participation in complexes 3-6 was drawn from the in-depth and comparative DFT study. The reactivity of the imido and amido complexes with CO2 was probed, and conclusions about the influence of the formal oxidation state are reported.

Molecular and electronic structure of dinuclear uranium bis-μ-oxo complexes with diamond core structural motifs. - Schmidt, Anna-Corina; Heinemann, Frank Wilhelm; Lukens, Wayne W.; Meyer, Karsten (Journal of the American Chemical Society, 2014)
In a multiple-bond metathesis reaction, the triazacyclononane (tacn)-anchored methyl- and neopentyl (nP)-substituted tris(aryloxide) U(III) complex [(((nP,Me)ArO)3tacn)U(III)] (1) reacts with mesityl azide and CO2 to form mesityl isocyanate and the dinuclear bis(μ-oxo)-bridged U(V)/U(V) complex [(((nP,Me)ArO)3tacn)U(V)2(μ-O)2] (3). This reaction proceeds via the mononuclear U(V) imido intermediate [(((nP,Me)ArO)3tacn)U(V)(NMes)] (2), which has been synthesized and fully characterized independently. The dimeric U(V) oxo species shows rich redox behavior: complex 3 can be reduced by one and two electrons, respectively, yielding the mixed-valent U(IV)/U(V) bis(μ-oxo) complex [K(crypt)][(((nP,Me)ArO)3tacn)U(IV/V)2(μ-O)2] (7) and the U(IV)/U(IV) bis(μ-oxo) complex K2[(((nP,Me)ArO)3tacn)U(IV)2(μ-O)2] (6). In addition, complex 3 can be oxidized to provide the mononuclear uranium(VI) oxo complexes [(((nP,Me)ArO)3tacn)U(VI)(O)eq(OTf)ax] (8) and [(((nP,Me)ArO)3tacn)U(VI)(O)eq]SbF6 (9). The unique series of bis(μ-oxo) complexes also shows notable magnetic behavior, which was investigated in detail by UV/vis/NIR and EPR spectroscopy as well as SQUID magnetization studies. In order to understand possible magnetic exchange phenomena, the mononuclear terminal oxo complexes [(((nP,Me)ArO)3tacn)U(V)(O)(O-pyridine)] (4) and [(((nP,Me)ArO)3tacn)U(V)(O)(O-NMe3)] (5) were synthesized and fully characterized. The magnetic study revealed an unusually strong antiferromagnetic exchange coupling between the two U(V) ions in 3. Examination of the (18)O-labeled bis(μ-oxo)-bridged dinuclear complexes 3, 6, and 7 allowed for the first time the unambiguous assignment of the vibrational signature of the [U(μ-O)2U] diamond core structural motif.

Uranium-mediated reductive conversion of CO2 to CO and carbonate in a single-vessel, closed synthetic cycle - Schmidt, Anna-Corina; Nizovtsev, Alexey; Scheurer, Andreas; Heinemann, Frank Wilhelm; Meyer, Karsten (Chemical Communications, 2012)
The new neopentyl (Neop)-substituted tris(aryloxide) U(iii) complex [((ArO)tacn)U] reacts with CO to form CO and the bridging carbonate complex [(( ArO)tacn)U(μ-CO )]. The uranium(iv) bridging oxo [((ArO) tacn)U(μ-O)] has been determined to be the intermediate in this reaction. For the first time, both U(iv) complexes can be reduced back to the U(iii) starting material. Thus, with KC as reductant, [((ArO)tacn)U] engages in a synthetic cycle, in which CO is converted to CO and CO . © 2012 The Royal Society of Chemistry.